2020
DOI: 10.1021/acs.molpharmaceut.0c00389
|View full text |Cite
|
Sign up to set email alerts
|

Self-Emulsifying Drug Delivery Systems: Hydrophobic Drug Polymer Complexes Provide a Sustained Release in Vitro

Abstract: The aim of this study was to develop hydrophobic ionic drug polymer complexes in order to provide sustained drug release from self-emulsifying drug delivery systems (SEDDS). Captopril (CTL) was used as an anionic model drug to form ionic complexes with the cationic polymers Eudragit RS, RL, and E. Complexes of polymer to CTL charge ratio 1:1, 2:1, and 4:1 were incorporated in two SEDDS, namely FA which was 40% Kolliphor RH 40, 20% Kolliphor EL, and 40% castor oil and FB, which was 40% Kolliphor RH 40, 30% glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Polymeric materials, particularly hydrogels, have been described as the preferred choice due to characteristics such as hydrophilic porous matrix, flexibility, high biocompatibility and biodegradability, prolonged consistency, userfriendliness, low cost, and ease of access [20][21][22]. To aid in finding its optimal parameters, there have been several experimental and in silico studies that confirm a strong dependency on solubility, high degree of functional design space, surface multivalency, facile chemical modification, high stability, and ease of integration with other materials such as lipids and nanoparticles [23][24][25][26]. For instance, Mdlovu et al designed a magnetic nanocarrier composed of iron oxide magnetic nanoparticles coated with Pluronic F127 for the delivery of the chemotherapeutic drug doxorubicin (DOX) in neuroblastoma where the drug release profile showed a pH-dependent drug release where more DOX was released under acidic environments than in neutral conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric materials, particularly hydrogels, have been described as the preferred choice due to characteristics such as hydrophilic porous matrix, flexibility, high biocompatibility and biodegradability, prolonged consistency, userfriendliness, low cost, and ease of access [20][21][22]. To aid in finding its optimal parameters, there have been several experimental and in silico studies that confirm a strong dependency on solubility, high degree of functional design space, surface multivalency, facile chemical modification, high stability, and ease of integration with other materials such as lipids and nanoparticles [23][24][25][26]. For instance, Mdlovu et al designed a magnetic nanocarrier composed of iron oxide magnetic nanoparticles coated with Pluronic F127 for the delivery of the chemotherapeutic drug doxorubicin (DOX) in neuroblastoma where the drug release profile showed a pH-dependent drug release where more DOX was released under acidic environments than in neutral conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Self-emulsifying drug delivery systems (SEDDS) are homogeneous mixtures of oils, surfactants, and cosolvents that emulsify upon aqueous dilution to improve lipophilic drug solubility, absorption, and controlled release ( 28 , 29 ). The majority of SEDDS have been developed to increase oral bioavailability, including FDA-approved Sandimmune Neoral.…”
Section: Discussionmentioning
confidence: 99%
“…The use of GRAS-type excipients with the least possible surfactant and cosurfactant (or co-solvent) ratios should be taken into consideration to assure that the final formulation is cytocompatible. As with other lipid-based formulations, the particle size relies on the excipients’ hydrophile–lipophile balance (HLB) value, where it is usually found that the higher the HLB value is, the lower the PS and Đ are, while the ZP charge is usually negative due to the presence of anionic surfactants and fatty acids unless specific lipids that grant the positive charge to the developed system are specifically employed, such as cationic surfactants, namely, tertiary amine surfactant, oleylamine, and the quaternary ammonium surfactants or polymers (e.g., Eudragit RS or RL) [ 196 , 197 ]. Incipient reports suggested that SEDDs could increase materials’ liver uptake [ 198 , 199 ], with further studies recommended on the cytocompatibility and mechanism behind such increment.…”
Section: Opportunities and Limitations Of Nanosystems For Mafld Thmentioning
confidence: 99%